8x+13=11x+13

Simple and best practice solution for 8x+13=11x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+13=11x+13 equation:



8x+13=11x+13
We move all terms to the left:
8x+13-(11x+13)=0
We get rid of parentheses
8x-11x-13+13=0
We add all the numbers together, and all the variables
-3x=0
x=0/-3
x=0

See similar equations:

| 3(3y+1)=9(y-2)+21 | | 0=2x^2+x-16 | | 6-(2z+4)=5-z | | 4(2w-1)=-10(1w-5) | | 10x-(7x-4)=16 | | -6(2b+1)+(13b-7-)=0 | | -6(2b+1)+(13b-7=0 | | (51+x)/9=4.5 | | 2(x-1)-6x=10-2(x+4) | | -(-6k+1)+2(-3k+4)=7k+7 | | 8(=u+7) | | 8=(u+7) | | 10x=2.4 | | 8(x+1)=1+8x | | -205=-6(2+8x)-1 | | 2x2-3x-189=0 | | 0.1-0.03(x+3)=-0.02(2-x) | | 7(2b-3)=-133 | | 8(-8+8n)=-64 | | 3+3/4x=81 | | 1+3(5z-3)=-5(5z+6)+3 | | -6-3(-3+4x)=-93 | | 8(w-5)+4w=-28 | | 5x-3/2-x=7 | | 8w+11=−7 | | -8(7x+8)=-288 | | -9=6-(7-a) | | 5(u-6)-8u=-12 | | X+7x-5=46 | | 16=3-(n+8) | | 5/3y-3=32 | | -5x+15-2x=46-4x-4 |

Equations solver categories